Management of Research Infrastructures: A South African Funding Perspective - Ramoutar-Prieschl, Rakeshnie (Springer Nature, 2020)
This open access book provides an overview of the building blocks necessary for managing, steering and guiding the establishment of a research infrastructure (RI). It offers valuable insights into RI investment, access and management at the academic, grants management, agency and policy level, and serves as a useful guide for the research community, students, and those in the private sector wishing to understand the approaches and opportunities involved in the establishment, maintenance and management of research infrastructure platforms. Presenting a holistic view of RI investment and granting cycles from a South African perspective, the book's target audience includes those working in science diplomacy, policymaking and science grants councils (especially in Africa) as well as funders and donors.